2012
DOI: 10.1155/2012/598789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artificial Flooding for Hydroelectric Development on the Population ofMansonia humeralis(Diptera: Culicidae) in the Paraná River, São Paulo, Brazil

Abstract: The closure of two phases of the dam at the Porto Primavera Hydroelectric Plant on the Paraná River flooded a flawed system located in the Municipality of Presidente Epitácio, São Paulo state, favoring the proliferation of aquatic weeds. This study aimed to observe the population of Mansonia humeralis in the area, monitoring the richness, diversity, and dominance of this species both before and during different phases of reservoir flooding as well as evaluate its possible consequences concerning human and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…The effect of the reservoir did not infl uence the species dominance (i.e., all species were proportionally affected). Paula (11) reported similar results regarding the dominance of mosquitoes in hydroelectric project areas.…”
Section: Discussionsupporting
confidence: 55%
“…The effect of the reservoir did not infl uence the species dominance (i.e., all species were proportionally affected). Paula (11) reported similar results regarding the dominance of mosquitoes in hydroelectric project areas.…”
Section: Discussionsupporting
confidence: 55%
“…Ae. scapularis and mosquitoes in tribe Mansoniini are examples of culicids that are indicative of environments that have undergone major changes antropic, oscillating between presence or absence (Dorvillé 1995, Paula et al 2012 Although the parks studied here contain fragments of native forests, their location within built-up areas, the changes made to accommodate the parks and their users and the presence of humans in large numbers in and around them mean that these areas are under environmental stress. We found that Ae.…”
Section: Discussionmentioning
confidence: 99%
“…: 84-912800896. Email: giangnt@vnu.edu.vn https://doi.org/10.25073/2588-1094/vnuees.4217 gây ra hiện tượng xâm nhập mặn [1], ảnh hưởng đến hệ sinh thái [2] hoặc có thể gây ra lũ lụt nhân tạo do vận hành điều tiết hồ không hợp lý [3], đặc biệt là các hiện tượng bồi lấp sạt lở bờ sông và cửa sông do sự mất cân bằng bùn cát gây ra bởi hệ thống hồ chứa [4].…”
Section: đặT Vấn đềunclassified
“…: 84-912800896. Email: giangnt@vnu.edu.vn https://doi.org/10.25073/2588-1094/vnuees.4217 gây ra hiện tượng xâm nhập mặn [1], ảnh hưởng đến hệ sinh thái [2] hoặc có thể gây ra lũ lụt nhân tạo do vận hành điều tiết hồ không hợp lý [3], đặc biệt là các hiện tượng bồi lấp sạt lở bờ sông và cửa sông do sự mất cân bằng bùn cát gây ra bởi hệ thống hồ chứa [4].Các nghiên cứu thể giới đã chỉ ra rằng hệ thống hồ chứa trên sông gây tác động lớn đến vùng hạ du. Các tác động tiêu cực này xảy ra nghiêm trọng hơn tại các vùng đồng bằng châu thổ, nơi được hình thành và nuôi dưỡng bởi lượng lớn bùn cát sông (phù sa).…”
unclassified